Gestão de aquíferos impactados por necrópoles - Sousa, Mauro César de Brito (2015)
If inappropriately located or insufficiently protected, the necropolis mean an important problem for public health and contamination risks to aquifers. In Teresina, Piauí, the case of the cemetery Areias, located near the Parnaíba River and close to the water intake for public supply, calls attention to negligence the management of contaminated areas and reflects the current state of aquifers management impacted by necropolis in Brazil. This study indicated the appropriate form of investigation environmental liabilities caused by necropolis. In addition, used the computer modeling of aquifers to improve the diagnosis of contamination, adapting solutions to ensure the quality and simplicity of the model. Furthermore, this study proposed the implementation of devices to improve the licensing criteria set by CONAMA Resolution 368/2006. The results showed that the use of the suggested steps can help manage aquifers impacted by necropolis and prevent the development of new environmental liabilities in urban areas